IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KOTA PADANG PANJANG NOMOR 2 TAHUN 2014 TENTANG KAWASAN TANPA ROKOK TAHUN 2014-2015 - Wardhana, M. Yollan Vierta; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study was purposed to understand the implementation process of Regional Policy number 02 year 2014 on the regulation of smoke free area in Padang Panjang. This policy was aimed to protect public health from the dangerous effects of smoking, to protect passive smokers i.e women, children and adolescents, also decreasing number of the new smokers. This policy was one of many solutions to increasing amount of fresh and clean air in this area. To achieve the vision of Padang Panjang city to improving the quality of public health. This study was held in Padang Panjang. This study was a qualitative with descriptive methods. Data were collected by the writer using interview technique, observation and documentation. With using the key informant as the information source by seeing the phemonenons in the legal files. The results showed the implementation of Regional Policy number 02 year 2014 on the regulation of smoke free area in Padang Panjang was effectively successful. The policy received strong supports from public because its positive effects. One of the main factors contributed to the successfulness of the implementation of smoke free policy is the good cooperation between various elements in the community like government and the society.Keywords : Policy Implementation, City Regulation, Smoke Free Area, Padang Panjang City